APPLICATION OF THE GO TO YOUR POST METHOD (MOVING IN THE CHOSEN DIRECTION) TO IMPROVE THE THEMATIC LEARNING OUTCOMES OF CLASS IV STUDENTS 001 STATE PRIVATE SCHOOL - Rosdiyani Rosdiyani; Eka Yanti; Rejeki Rejeki (Indonesian Journal of Basic Education, 2021)
This study aims to find out that the application of the go to your post method (moving in the chosen direction) to improve thematic learning outcomes of Class IV SD Negeri 001 students is widespread. The background of this research is the failure to achieve the learning objectives as illustrated by the daily test scores of students in thematic learning of only 27 students. The subjects who received the action in this study were the fourth grade students in the Odd semester 2021/2022 as many as 27 students. The data analysis technique used is the model of collecting several student activity sheets, research, and question sheets. The results of this study were seen from the first cycle of the first meeting to 27 students 46% who reached the KKM. In the first cycle, the second meeting also experienced an increase again, as many as 27 students 58%. In the second cycle of the first meeting, it was found that student learning outcomes increased again from 27 (63%) students who had reached the KKM. At the second meeting, students' learning outcomes were very satisfactory, namely from 27 students (87%). The conclusion of this study is that the application of the go to your post method (moves in the chosen direction) to improve students' thematic learning outcomes Class IV SD Negeri 001 is encroached